BEAMS: a workforce development program to bridge the gap between biologists and material scientists - Lee, Marilyn S (Synth Biol (Oxf), 2020)
To maximize innovation in materials science and synthetic biology, it is critical to master interdisciplinary understanding and communication within an organization. Programming aimed at this juncture has the potential to bring members of the workforce together to frame new networks and spark collaboration. In this article, we recognize the potential synergy between materials and synthetic biology research and describe our approach to this challenge as a case study. A workforce development program was devised consisting of a lecture series, laboratory demonstrations and a hands-on laboratory competition to produce a bacterial cellulose material with the highest tensile strength. This program, combined with support for infrastructure and research, resulted in a significant return on investment with new externally funded synthetic biology for materials programs for our organization. The learning elements described here may be adapted by other institutions for a variety of settings and goals.